2020
DOI: 10.1039/d0ta06485h
|View full text |Cite
|
Sign up to set email alerts
|

A Cu and Fe dual-atom nanozyme mimicking cytochrome c oxidase to boost the oxygen reduction reaction

Abstract: The intrinsically sluggish kinetics of oxygen reduction reaction (ORR) and overuse of expensive and unstable Pt-based catalysts have severely hampered the development of clean energy technologies. Herein, a type of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
116
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(116 citation statements)
references
References 48 publications
0
116
0
Order By: Relevance
“…A dominant EXAFS FT peak founded in the related fitting curves of Cu SAs/CN around 1.44 Å can be ascribed as the Cu—N scattering path. [ 30 , 32 , 33 ] Whereas no Cu—Cu coordination peak at 2.2 Å can be observed, suggesting that Cu exists as an isolated atom that is atomically dispersed on the CN matrix. [ 29 ] Meanwhile, the EXAFS fitting curves perfectly reproduced the experimental EXAFS FT experimental curves of Cu SAs/CN (Figure 1f and Figure S8 , Supporting Information), Cu foil and CuO (Figure S9 , Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…A dominant EXAFS FT peak founded in the related fitting curves of Cu SAs/CN around 1.44 Å can be ascribed as the Cu—N scattering path. [ 30 , 32 , 33 ] Whereas no Cu—Cu coordination peak at 2.2 Å can be observed, suggesting that Cu exists as an isolated atom that is atomically dispersed on the CN matrix. [ 29 ] Meanwhile, the EXAFS fitting curves perfectly reproduced the experimental EXAFS FT experimental curves of Cu SAs/CN (Figure 1f and Figure S8 , Supporting Information), Cu foil and CuO (Figure S9 , Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that the binding energy of M‐N x in Cu/Fe−NC exhibits a negative shift of 0.12 eV and positive shift of 0.15 eV as compared with Fe−N−C and Cu−N−C, respectively, which indicates Cu species donor electrons to N x ‐Fe configuration and Fe species withdraw electrons from Cu‐N x sites. Profiting from above electronic mobility of Cu→Fe, local electron transfer may have occured, which further attract intermediates of ORR [14d,25] . In addition, the Cu/Fe−NC possesses the highest fraction of C−N according to C 1s deconvolution (17.05 %, Figure S6) and the highest total fraction of active N dopants (62 % from pyridinic‐N, M−N and graphitic‐N) among the four materials (Figure 3d and Table S3), which is attributed to the modulation of micro‐meso porous structure to be beneficial for N coordination and configuration [18b,26] …”
Section: Resultsmentioning
confidence: 98%
“…Nevertheless, Pt‐based catalysts also have severely hampered the development of AABs, which is caused by the high cost, limited resources, Pt dissolution, and carbon corrosion in strong alkaline medium. [ 9,10 ] To address these issues, it is urgent to explore and develop efficient and durable nonprecious metal ORR electrocatalysts to substitute Pt usage.…”
Section: Introductionmentioning
confidence: 99%